Implications of achieving the quality of financial reports on the opinion of the external auditor )An applied study on a sample of Iraqi local organizations( - Abdul Salam Abdullah Jassim; Mr. Dr. Qamar Mr. Ahmed (Scholar Express Journals, 2023)
This study aimed to identify the implications of achieving the quality of financial reports on the opinion of the external auditor of a sample of Iraqi local organizations According to the analytical descriptive approach and on the electronic form that was distributed to an intentional sample of (170) auditors . The most important results of the research are: the existence of a positive effect for each of the relevance, reliability, comparability, stability, and comprehensibility of the information on the opinion of the external auditor, and that local organizations contribute to providing the information that users need through financial reports that contribute to identifying the problems that the administration faces during work. In addition to assisting the administration in taking the necessary decisions to determine the need for employees and other issues, as the information obtained is returned to the decision-making centers according to their needs
Keywords: Quality of financial reports; external auditor; auditors; Iraqi local organizations